Does uterine manipulator type affect surgical outcomes of laparoscopic hysterectomy? - Ali Yavuzcan; Raşit Altıntaş; Gazi Yıldız; Alper Başbuğ; Merve Baştan; Mete Çağlar (Wolters Kluwer Medknow Publications, 2021)
Objectives: Many surgeons use uterine manipulator (UM) during laparoscopic hysterectomy (LH). In this study, we aimed to compare the outcomes of LH operations performed by using partially reusable UM with the articulated system (artUM) and disposable (dUM) UM without articulation. Materials and Methods: A total of 99 patients underwent the LH operation. This study was carried out with 35 of those 99 Caucasian patients who met the inclusion criteria. Group 1 consisted for 7 LH operations using the articulated RUMI®II/KOH-Efficient™ (Cooper Surgical, Trumbull, CT, USA) system (artUM), while Group II consisted of 28 patients using old-type V Care® (ConMed Endosurgery, Utica, New York, USA) dUM as UM. Results: Mean operation time was found to be 157.1 ± 42.0 min. The operation time was found statistically longer in Group 1, consisted of artUM used patients (P = 0.006 and P < 0.05). No statistically significant difference was found between two groups in terms of surgical results such as, delta hemoglobin value (P = 0.483 and P < 0.05), length of hospital stay (P = 0.138 and P < 0.05), and postoperative maximum body temperature (P = 0.724 and P < 0.05). Conclusion: The UM type did not alter the surgical outcomes except the operating time in our study. According to our results, the surgical technique is a more significant variable than instruments used in LH for normal size uterus. Further prospective, large-scale studies comparing various UM systems are mandatory.